2000
DOI: 10.1016/s0008-6223(99)00290-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and electronic properties of donor-linked fullerenes

Abstract: Synthesis and electronic properties of donor-linked fullerenes towards photochemical molecular devices Nierengarten, J.F.; Eckert, J.F.; Felder, D.; Nicoud, J.F.; Armaroli, N.; Marconi, G.; Vicinelli, V.; Boudon, C.; Gisselbrecht, J.P.; Gross, M. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://ww… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 85 publications
5
21
0
Order By: Relevance
“…The copper-terpy MLTC excited state was quenched via electron transfer to the fullerene moieties, leading to the C 60 − [Cu(phen) 2 ] 2 + C 60 charge-separated state. The effect of an increasing amount of fullerene groups around a photoactive copper complex was studied by Armaroli and coworkers [69,88]. A range of structures based on a bis(1,10-phenanthroline) copper(I) core surrounded by 4, 8 and 16 fullerene units was prepared (76-78, Fig.…”
Section: Copper and Platinum Complexesmentioning
confidence: 99%
“…The copper-terpy MLTC excited state was quenched via electron transfer to the fullerene moieties, leading to the C 60 − [Cu(phen) 2 ] 2 + C 60 charge-separated state. The effect of an increasing amount of fullerene groups around a photoactive copper complex was studied by Armaroli and coworkers [69,88]. A range of structures based on a bis(1,10-phenanthroline) copper(I) core surrounded by 4, 8 and 16 fullerene units was prepared (76-78, Fig.…”
Section: Copper and Platinum Complexesmentioning
confidence: 99%
“…[7] Indeed, systems combining fullerene accepting moieties with all kinds of donors have generated a great deal of attention. [7,8,35] Spectacular covalent and noncovalent fullerene-donor conjugates have already been prepared and systematic studies on their electronic properties revealed interesting photoinduced processes. Moreover, photovoltaic devices prepared from such hybrid compounds have also shown promising energy-conversion efficiencies.…”
Section: Photoactive Clicked Fullerene Derivativesmentioning
confidence: 99%
“…[5][6][7] The post-functionalization of fullerene building blocks is far less popular. [8] This can be explained by the chemical reactivity of the fullerene subunit, which limits the range of reactions that can be used for the further chemical transformation of C60 derivatives. [5] Nonetheless, esterification, [9] amidification, [10] and condensation [11] reactions have been useful for transforming fullerene derivatives into sophisticated molecular structures.…”
Section: Introductionmentioning
confidence: 99%
“…Significant increases in the lifetime of the charge separated states were observed upon coordinating nitrogenous axial ligands to the latter. <Chemical Structure 8> Likewise, different types of non-covalently and covalently linked copper phthalocyaninefullerene dyads have been prepared (Li et al 2004b, Nierengarten et al 2000, El-Khouly et al 2002). An example is a series of fulleropyrrolidinophthalocyanines containing free base, Zn and Cu used as electron-donating building blocks in fullerene dyes of type 22 .…”
Section: Donor-acceptor Electron Transfer Compoundsmentioning
confidence: 99%